A novel rare variant in SCN1Bb linked to Brugada syndrome and SIDS by combined modulation of Nav1.5 and Kv4.3 channel currents - Hu, Dan; Veltmann, Christian; Schimpf, Rainer; Borggrefe, Martin (Heart rhythm, 2012)
Background - Cardiac sodium channel β-subunit mutations have been associated with several inherited cardiac arrhythmia syndromes. - Objective - To identify and characterize variations in SCN1Bb associated with Brugada syndrome (BrS) and sudden infant death syndrome (SIDS). - Methods - All known exons and intron borders of the BrS-susceptibility genes were amplified and sequenced in both directions. Wild type (WT) and mutant genes were expressed in TSA201 cells and studied using co-immunoprecipitation and whole-cell patch-clamp techniques. - Results - Patient 1 was a 44-year-old man with an ajmaline-induced type 1 ST-segment elevation in V1 and V2 supporting the diagnosis of BrS. Patient 2 was a 62-year-old woman displaying a coved-type BrS electrocardiogram who developed cardiac arrest during fever. Patient 3 was a 4-month-old female SIDS case. A R214Q variant was detected in exon 3A of SCN1Bb (Nav1B) in all three probands, but not in any other gene previously associated with BrS or SIDS. R214Q was identified in 4 of 807 ethnically-matched healthy controls (0.50%). Co-expression of SCN5A/WT + SCN1Bb/R214Q resulted in peak sodium channel current (INa) 56.5% smaller compared to SCN5A/WT + SCN1Bb/WT (n = 11-12, P<0.05). Co-expression of KCND3/WT + SCN1Bb/R214Q induced a Kv4.3 current (transient outward potassium current, Ito) 70.6% greater compared with KCND3/WT + SCN1Bb/WT (n = 10-11, P<0.01). Co-immunoprecipitation indicated structural association between Navβ1B and Nav1.5 and Kv4.3. - Conclusion - Our results suggest that R214Q variation in SCN1Bb is a functional polymorphism that may serve as a modifier of the substrate responsible for BrS or SIDS phenotypes via a combined loss of function of sodium channel current and gain of function of transient outward potassium current.